Full‐field energy‐dispersive powder diffraction imaging using laboratory X‐rays. (1st February 2015) - Egan, Christopher K.; Jacques, Simon D. M.; Wilson, Matthew D.; Veale, Matthew C.; Seller, Paul; Withers, Philip J.; Cernik, Robert J.
<x xml:space="preserve">Abstract</x> A laboratory instrument with the ability to spatially resolve energy‐dispersed X‐ray powder diffraction patterns taken in a single snapshot has been developed. The experimental arrangement is based on a pinhole camera coupled with a pixelated spectral X‐ray detector. Collimation of the diffracted beam is defined by the area of the footprint of a detector pixel and the diameter of the pinhole aperture. Each pixel in the image, therefore, contains an energy‐dispersed powder diffraction pattern. This new X‐ray imaging technique enables spatial mapping of crystallinity, crystalline texture or crystalline phases from within a sample. Validation of the method has been carried out with a back‐to‐back comparison with crystalline texture mapping local to a friction stir weld in an aluminium alloy taken using synchrotron radiation.